Efectos del entrenamiento en superficies inestables sobre el equilibrio y funcionalidad en adultos mayores (2015)
ABSTRACT: To determine the effects of an eight-week training program on unstable surfaces with and without strength work regarding balance and functional capacity in adults over 60 who belong to the inder sport schools program in Medellín. Methodology: simple single-blind and masked experimental trials were conducted on 34 subjects who were randomly assigned to two intervention groups with and without strength work on unstable surfaces. Unipodal and bipodal balance was measured while the subjects' eyes were open and closed. In addition, functional tests such as Up and Go, Arm Curl and Chair Test were conducted. Results: interventions with and without strength work improved total balance in 57.0 and 69.5 seconds respectively. The differences between the groups were not statistically significant (p = 0.33), nonetheless they were important. Conclusion: both interventions improve balance, however there are differences that are important in practice. These differences favor the program involving unstable surfaces without an unstable without strength work because the intervention has a better effect on unipodal and bipodal balance both with open and closed eyes.